Comparison of advanced authorisation infrastructures for grid computing - Stell, A.J.; Sinnott, R.O.; Watt, J.P. (19th International Symposium on High Performance Computing Systems and Applications (HPCS'05), 2005)
The widespread use of grid technology and distributed compute power, with all its inherent benefits, will only be established if the use of that technology can be guaranteed efficient and secure. The predominant method for currently enforcing security is through the use of public key infrastructures (PKI) to support authentication and the use of access control lists (ACL) to support authorisation. These systems alone do not provide enough fine-grained control over the restriction of user rights, necessary in a dynamic grid environment. This paper compares the implementation and experiences of using the current standard for grid authorisation with Globus - the grid security infrastructure (GSI) - with the role-based access control (RBAC) authorisation infrastructure PERMIS. The suitability of these security infrastructures for integration with regard to existing grid technology is presented based upon experiences within the JISC-funded DyVOSE project.